»Truth« and Fiction Conspiracy Theories in Eastern European Culture and Literature - Deutschmann, Peter; Herlth, Jens; Woldan, Alois (Edition Kulturwissenschaft, 2020)
Several of the most prolific and influential conspiracy theories have originated in Eastern Europe. The far reaching influence of conspiracy narratives can be observed in recent developments in Poland or with regard to the wars waged in Eastern Ukraine and in former Yugoslavia. This volume analyses the history behind this widespread phenomenon as well the role it has played in Eastern European cultures and literature both past and present.